A Case Study on Investment Decisions of Madhur Oil Company - Bansal, Surbhi (Journal of Commerce and Trade, 2017)
Modern managers are doing such financial and investment planning in a different way. In their concept, it does not mean capitalisation and capital structure of the organisation, but also it includes the determination of the organisation’s investment decisions, investment policies and investment procedures. The purpose of research is to survey and analyse some different behaviour in the process of an organisation or a different aspect which can benefit the mass in future. Hence, the present paper makes a case study on investment decisions of Madur Oil Company. Madur Oil Company has earned 139% ROI and got reduced cost of production. There is also a saving in manpower and saving of oil which reduces overall cost of production which shows favourable situation to undertake the project.. JEL Classification : G 31, G 32.